İmalat İşletmelerinde Enerji Verimliliğinin Yapısal Eşitlik Modeli İle İncelenmesi - Şenol, Leyla; Akman, Gülşen (Muş Alparslan Üniversitesi, 2019)
The purpose of this study is to contribute to the subject of usingenergy efficiently and economizing energy consumption as well as to raiseawareness about this issue. With this object in mind, data has been gatheredfrom manufacturing businesses through survey management in order to determinethe degree of influence of the factors that affect energy efficiency and tomake sure whether there is a relationship between them.  As a result of the factor analysis, fivefactors have been detected. According to the Structural Equation Modelling, there has not been found a statistically meaningful relationship betweenautomatization and energy efficiency. However, it has been understood thatthere is a positive and statistically meaningful relationship between energyefficiency and education as well as between supervision and management. Theimportance of educating the employees, conducting an inspection and the factorof management has been emphasized so as to use energy efficiency and eonomizeenergy consumption. In this respect, awareness for energy efficiency must beimproved in all levels, in addition to the existing energy policies energysaving policies must be formed, and control must be provided through inspectionmechanism.

Bu çalışmanın amacı, enerjinin verimli kullanılması ve tasarrufunsağlanması konusunda katkı sağlamak ve farkındalık yaratmaktır. Bu amaçlaimalat işletmelerinden enerji verimliğini etkileyen etmenlerin etkiderecelerini ve aralarında ilişki olup olmadığının belirlenmesi için anketyönetimi ile veri toplanmıştır. Faktör analizi sonucunda beş faktörbelirlenmiştir. Yapısal Eşitlik modeli analizine göre, otomasyon ve enerjiverimliliği arasında istatistiksel olarak anlamlı bir ilişki bulunmamıştır.Ancak, enerji verimliliği ile eğitim, denetim ve yönetim arasında pozitif yöndeve istatistiksel olarak anlamlı bir ilişki olduğu belirlenmiştir. Enerjininverimli kullanılması ve tasarrufun sağlanması için, çalışanlara eğitimverilmesi, denetimin yapılması ve yönetim faktörünün önemi ortaya konmuştur. Bubağlamda Enerji verimliliği bilinci her düzeyde geliştirilmeli, var olan enerjipolitikalarına ilave enerji tasarrufu politikaları oluşturulmalı ve denetimmekanizması ile kontrol sağlanmalıdır.
Investigation of Energy Efficiency in Manufacturing Enterprises Through Structural Equation Model
anemon
Keywords: Energy; Efficiency; Management; Saving; Enterprise; verimlilik; tasarruf; İşletme; Enerji; Yönetim